Hajj Participant Monitoring System Using GPS with Internet of Things (IOT) Based on Cloud Computing - Muhammad Rifky Saiful Qadr; Ari Purno Wahyu Wibowo (Publikasi Indonesia, 2024)
The monitoring and coordination of Hajj participants pose significant challenges, especially in ensuring their safety and managing their mobility efficiently. This research focuses on the development and implementation of a web-based system that integrates GPS and Internet of Things (IoT) technology to monitor the real-time location of Hajj participants. The system leverages GPS to track participant locations accurately, enhancing safety and optimizing participant mobility management. IoT devices are integrated into the system to collect data related to participants' locations and conditions, which are then transmitted to a secure server for seamless access through the web platform. The system's design emphasizes providing an intuitive user interface, making it easier for administrators to manage, coordinate, and respond to participant needs effectively. The web-based platform offers structured and user-friendly data visualization through features like interactive maps and condition dashboards. These tools enable rapid decision-making, improved logistical arrangements, and effective participant coordination. This study highlights the importance of secure and stable IoT configurations to ensure continuous data updates and accessibility under various conditions. The findings demonstrate that the integration of GPS and IoT with a cloud-based platform significantly enhances the management of Hajj participants, providing a robust and scalable solution for real-time monitoring, efficient coordination, and improved safety. The proposed system contributes to advancing technological solutions in large-scale religious gatherings, offering practical implications for future applications in similar contexts.